2013
DOI: 10.12788/j.suponc.0009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of skin reactions and pain reported by patients receiving radiation therapy for cancer at different sites

Abstract: Background Skin reactions and pain are commonly reported side effects of radiation therapy (RT). Objective To characterize RT-induced symptoms according to treatment site subgroups and identify skin symptoms that correlate with pain. Methods A self-report survey, adapted from the MD Anderson Symptom Inventory and the McGill Pain Questionnaire, assessed RT-induced skin problems, pain, and specific skin symptoms. Wilcoxon Sign Ranked tests compared mean severity of pre- and post-RT pain and skin problems wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Throughout the course of the study, patients reported their pain intensity at the RT site on a scale of 0 to 10 in a self-report daily Pain Diary. The Skin-Pain Inventory was a 16-item questionnaire that evaluated the severity of skin problems and pain at the RT site, as well as 9 specific pain symptoms (i.e., itchy, achy, tender, hot-burning, tight, redness, flaking, bumpy) on a 6-point severity scale anchored by 0 ("Not Present") and 5 ("Very Severe") [11]. A Feedback Questionnaire consisted of 12 questions regarding likes and dislikes of the topical agent, perceived benefit for skin reactions or pain, use of standard care topical treatments, and their perceived assigned study arm.…”
Section: Study Procedures and Measuresmentioning
confidence: 99%
“…Throughout the course of the study, patients reported their pain intensity at the RT site on a scale of 0 to 10 in a self-report daily Pain Diary. The Skin-Pain Inventory was a 16-item questionnaire that evaluated the severity of skin problems and pain at the RT site, as well as 9 specific pain symptoms (i.e., itchy, achy, tender, hot-burning, tight, redness, flaking, bumpy) on a 6-point severity scale anchored by 0 ("Not Present") and 5 ("Very Severe") [11]. A Feedback Questionnaire consisted of 12 questions regarding likes and dislikes of the topical agent, perceived benefit for skin reactions or pain, use of standard care topical treatments, and their perceived assigned study arm.…”
Section: Study Procedures and Measuresmentioning
confidence: 99%
“…Because irradiation therapy damages healthy tissue and causes skin inflammation and treatment site pain, control of pain in these patients requires a more complex organization of therapeutic strategies. 20 Increasing pain documentation alone was not enough to significantly affect the prevalence of pain in these patients.…”
Section: Discussionmentioning
confidence: 88%
“…In severe cases when treating with high doses, skin breakdown may occur, leading to moist desquamation (MD) or, rarely, ulceration. 1 , 2 RD begins to appear in patients between 1 and 4 weeks into RT and peaks in severity 2–4 weeks after the completion of RT. 1 , 3 , 4 While acute RD can be extremely painful and uncomfortable, most patients recover within 3 months after the completion of RT.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 3 , 4 While acute RD can be extremely painful and uncomfortable, most patients recover within 3 months after the completion of RT. 2 However, RD can also persist chronically and may leave patients with permanent changes to their skin, such as dryness, hyperpigmentation, and telangiectasia. 5 These chronic changes may affect patients’ mobility, cause disfiguration, and negatively impact patient quality of life in the long term.…”
Section: Introductionmentioning
confidence: 99%